Identification of common gender roles and gender stereotypes in preschool children aged four to five - Arkoncel, Miguel Luis O.; Perez, Ma. Isabel A.; Infantado, Grace Marie A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
ABSTRACT The ambiguity of gender is brought about by its social definition. The development of children often happens at the confines of their society about gender. Different societies have different expectations when it comes to growing up male or female. Little is known when it comes to gender in the Philippine setting, especially in young children. This study explores the gender roles and the gender stereotypes that children aged four to five years old have. The researchers asked children from the UP CDC (University of the Philippines Child Development Center) to make a story with a male and female character using a map and took note of the roles that they give their male and female characters. The researcher also asked the children's teachers to answer a questionnaire containing questions about common gender roles that they have observed. Lastly, the researchers looked through the children's previous logs for excerpts that may or may not support the results from the storytelling. The study found that even though children attribute some roles to a specific gender, they do not collectively stereotype or limit roles to one gender. Therefore, teaching children about taking on a varied set of roles, despite the beliefs that they already know, will not elicit confusion nor hinder their development.
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Sex role in children -- Philippines